Pests of fruit crops : - Alford, David V. (Elsevier/Academic Press, 2007)
This book focuses on insects and mites affecting pome fruits, stone fruits, cane fruits and strawberries, bush fruits, hopss, vines, citrus fruits, nuts, figs, olives and more. The pests are considered in their natural sequence of less advanced to move advanced forms, including a description of each, its life history, plants affected and damage caused.